Maize Sheller A Low-Cost Solution for Smallholder Farmers in Zambia - Matin, M. A.; Mulundu, S.; Zingwari, O (2025)
The Maize Sheller is a low-cost and labour-saving shelling option for smallholder farmers. It can be used for fast shelling of maize. For a service provider, it is a machine that can generate good income for about 4–5 months after harvest but has some businesses in other months of the year (off-season). The diesel engine powered maize sheller is fast compared to manual shelling. While hand shelling can take about 14 labour-days to shell a ton of maize, the machine can do that in less than an hour. Thus, it drastically reduces drudgery, labour, time, and cost compared to manual shelling of maize. The sheller has a low cost of operation and maintenance.